Error-resilient image coding (ERIC) with smart-IDCT error concealment technique for wireless multimedia transmission - Yew-San Lee; Ong, K.-K.; Chen-Yi Lee (IEEE transactions on circuits and systems for video technology, 2003)
The fields of multimedia and wireless communications have grown rapidly, leading to a great demand for an image coding scheme that has both compression and error-resilient capabilities. Because bandwidth is a valuable and limited resource, the compression technique is applied to wireless multimedia communication. However, strong data dependency will be created while the bit-rate reduction is achieved. Transmission errors always results in significant quality degradation. An error-resilient image coding for discrete cosine transform-based image compression is proposed. It can successfully prevent errors from propagating across image block boundaries with little overhead. Additionally, a novel post-processing error concealment scheme is presented to retain low-frequency information and discard suspicious high-frequency information. Low-resolution information, rather than total corruption, can be obtained during the image-decoding process. Because of low complexity and latency properties, it is very suitable for wireless mobile applications. Simulation results show that good image quality (PSNR=31.78dB) and a low fraction of corruptive blocks (less than 5%) can be achieved even when the bit error rate is 0.1%.